PERAN GURU PAI DALAM MENCIPTAKAN PEMBELAJARAN YANG AKTIF, KREATIF, EFEKTIF, DAN MENYENANGKAN - Ginajeng Alif Tiharoh (JURNAL ILMIAH NUSANTARA, 2025)
Fiqh is not only material but also its application in daily life. However, the interest of fifth grade students in learning fiqh tends to be low. The reality in the field in fiqh learning is that many students only memorize the law, but have not been able to understand the meaning, purpose, and have not been able to practice it in daily life. Another challenge for Islamic Religious Education teachers is the periodic curriculum changes. This study aims to determine the role of Islamic Religious Education teachers in creating active, creative, effective, and enjoyable learning in fifth grade Islamic Religious Education subjects and what are the supporting and inhibiting factors at MI Muhamadiyyah 01 Sambong. This approach uses a descriptive qualitative approach. Data collection techniques include interviews, observations, and documentation. The results of the study show that Islamic Religious Education teachers in creating active, creative, effective, and enjoyable learning use varied learning. The methods used are shortening explanations, providing motivation, questions and answers, games, making projects, making posters, quizzes, and watching videos.